Environmental detection of Batrachochytrium dendrobatidis in a temperate climate - Walker, Susan F. (2007)
The aetiological agent of amphibian chytridiomycosis Batrachochytrium dendrobatidis is a primary cause of amphibian population declines. Current surveillance is based on the detection of B. dendrobatidis in its host but in vitro work suggests infective stages may survive in the abiotic environment for at least 3 mo. We describe here a surveillance system using filtration and quantita tive PCR that can detect B. dendrobatidis in small (<1 l) volumes of water. After assessing the analyt ical sensitivity of the protocol for both water and sediment samples in the laboratory, we analyzed environmental samples from the Sierra de Guadarrama mountain range in Spain at locations associ ated with chytrid-related die-offs and at other sites across Spain. B. dendrobatidis was detected in samples from 64% of the ponds in the Sierra de Guadarrama and at 2 sites outside this region, show ing that levels of amphibian exposure to B. dendrobatidis are spatially heterogeneous. In experimen tal microcosms, we detected B. dendrobatidis for up to 12 wk, though we found no evidence for an overall increase in biomass. Our results emphasise the need to further investigate the life cycle of B. dendrobatidis to more completely understand the epidemiology of this emerging pathogen.